Frequency of the SLCO1B1 388A>G and the 521T>C polymorphism in Tanzania genotyped by a new LightCycler®-based method - Aklillu, Eleni; Mugusi, Sabina; Ngaimisi, Eliford; Hoffmann, Michael Marcus; König, Sonja; Ziesenitz, Victoria C.; Mikus, Gerd; Haefeli, Walter E.; Weiß, Johanna (European journal of clinical pharmacology, 2011)
The 388A>G and the 521T>C polymorphism of the SLCO1B1 gene affect the activity of the uptake transporter OATP1B1, thus influencing kinetics, safety, and efficacy of substrate drugs. To evaluate the impact of these polymorphisms in populations of different ethnic origins, it is important to know their frequencies and to develop fast and reliable methods for genotyping. We therefore established a new, high-throughput method and determined the genotype and allelic frequencies of these polymorphisms in Tanzanians, for which the frequencies were unknown thus far.